In vivo site-directed mutagenesis of Neurospora crassa beta-tubulin gene by spheroplasts transformation with oligonucleotides - Mattia Calissano; Giuseppe Macino (Fungal Genetics Reports, 1996)
The use of Polymerase Chain Reaction (PCR) to incorporate mutated oligonucleotides into newly synthesized segments of DNA and the subsequent introduction of this DNA into competent cells is one of the most widely used methods of site-directed mutagenesis (Zoller et al.1984 DNA 3:479-488; Dalbodie-McFarland et al. 1982 Proc. Natl. Acad. Sci. USA 79:6409-6413). Several variations of this technique exist, but all require several and some time-consuming steps. Here we report the results of a rapid method of in vivo site-directed mutagenesis involving the direct transformation of Neurospora crassa spheroplasts with mutated oligonucleotides.